2004
DOI: 10.1002/rcm.1482
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen isotopomer site preference of N2O produced by Nitrosomonas europaea and Methylococcus capsulatus Bath

Abstract: Rapid Commun. Mass Spectrom. 2003; 17: 738-745.The calibration and calculation of the isotopomer composition of our internal N 2 O standard that was originally published has been revised. Because (Tables 1-4) do not change our conclusion that there is a significant difference in site preference of N 2 O formed during hydroxylamine oxidation by methanotrophic nitrification and by nitrification and nitrite reduction during nitrifierdenitrification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
146
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(166 citation statements)
references
References 5 publications
18
146
2
Order By: Relevance
“…Furthermore, much less variation was observed in the isotopic source signatures with values between −0.1±0.8 ‰ to −5.1±1.3 ‰ for SP s and 41.8 ± 0.9 ‰ to 23.2 ± 0.7 ‰ for δ 15 N bulk s . To calculate the net isotope effect (Sutka et al, , 2004(Sutka et al, , 2006Toyoda et al, 2005;Yoshida, 1988). The observed low N 2 O consumption agrees with a recent publication assuming that the N 2 O/(N 2 O + N 2 ) product ratio of denitrification is positively correlated with the NO − 3 availability in soils (Senbayram et al, 2011).…”
Section: Source Appointment By N 2 O Isotopomer Analysissupporting
confidence: 80%
See 1 more Smart Citation
“…Furthermore, much less variation was observed in the isotopic source signatures with values between −0.1±0.8 ‰ to −5.1±1.3 ‰ for SP s and 41.8 ± 0.9 ‰ to 23.2 ± 0.7 ‰ for δ 15 N bulk s . To calculate the net isotope effect (Sutka et al, , 2004(Sutka et al, , 2006Toyoda et al, 2005;Yoshida, 1988). The observed low N 2 O consumption agrees with a recent publication assuming that the N 2 O/(N 2 O + N 2 ) product ratio of denitrification is positively correlated with the NO − 3 availability in soils (Senbayram et al, 2011).…”
Section: Source Appointment By N 2 O Isotopomer Analysissupporting
confidence: 80%
“…This results in a net isotope effect ( δ 15 N bulk s ) between 5 and 26 ‰. According to pure culture studies, these values are characteristic for N 2 O produced by heterotrophic denitrification or nitrifier denitrification by ammonium oxidizing bacteria (Sutka et al, 2006(Sutka et al, , 2004Toyoda et al, 2005;Yoshida, 1988) Recent field studies confirm the importance of both processes for N 2 O production in soils (Kool et al, 2011;Wrage et al, 2001). In contrast, N 2 O produced by nitrifying bacteria leads to a significantly higher 15 N depletion with a net isotope effect ( δ 15 N bulk s = δ 15 N (NH + 4 )−δ 15 N bulk s ) between 46.9 ‰ (Sutka et al, 2006) and 68 ‰ (Yoshida, 1988).…”
Section: Source Appointment By N 2 O Isotopomer Analysismentioning
confidence: 91%
“…They also differ from three temperate agricultural soil incubation studies performed under conditions that favored nitrification, with site preference values that ranged from 17.3‰ to 23.3‰ (n = 9) [Well et al, 2008], also shown in Figure 4. However, the Pérez et al [2006] values are closer in magnitude to values measured for nitrifier denitrifying bacteria under nitrite and nitrate reduction of −7‰ to 2‰ (n = 26) [Sutka et al, 2006[Sutka et al, , 2003[Sutka et al, , 2004 (Figure 4).…”
supporting
confidence: 55%
“…An advantage of this new tracer is that it can potentially be used independently to differentiate between each microbial process without requiring knowledge of the 15 N composition of the substrates. Recent studies conducted in the laboratory cultures consisting of one or two species also showed significant differences in the site preference values for nitrification versus denitrification [Sutka et al, 2006[Sutka et al, , 2003[Sutka et al, , 2004Thompson et al, 2004;Toyoda et al, 2005]. The site preference values derived for denitrification are roughly in good agreement among the existing soils and bacteria studies, while those derived for nitrification appear to differ between those measured in the pure laboratory cultures and those in the incubation experiments of the natural environmental soils.…”
mentioning
confidence: 63%
See 1 more Smart Citation